Birth weight and subsequent body mass index in children: an international cross‐sectional study. Issue 4 (12th May 2016) - Mitchell, E. A.; Stewart, A. W.; Braithwaite, I.; Hancox, R. J.; Murphy, R.; Wall, C.; Beasley, R.; ,
Summary: Background: The reported association between birth weight and subsequent body mass index (BMI) is conflicting. Objectives: To examine the relationship between birth weight and BMI in children aged 6–7 years. Methods: Secondary analysis of data from a multi‐centre, multi‐country, cross‐sectional study (International Study of Asthma and Allergies in Childhood (ISAAC) Phase Three). Parents/guardians of children aged 6–7 years completed questionnaires about their children's birth weight, current height and weight and whether their mother smoked in the first year of the child's life. A general linear mixed model was used to determine the association between BMI and birth weight. Results: A total of 72 111 children (17 countries) were included in the analysis. There was a positive association of birth weight with BMI (for each kg increase in birth weight the BMI at 6–7 increased by 0.47 (SE 0.02) kg/m 2 ; p  < 0.0001) with a clear gradient by birth weight category. There was no statistically significant interaction between birth weight and Gross National Income (GNI). Conclusions: There is a positive linear relationship between birth weight and BMI in 6–7 year old children, which is present in both high and low income countries.